VALUE CO-CREATION IN HEALTHCARE SERVICE: A Systematic Literature Review - Purnami, Ni Made; Nurcaya, I Nyoman (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2023)
Value co-creation is crucial in business services as well as in healthcare services to enhance patient satisfaction. Active patient participation in value co-creation is critical in creating better and highly competitive services. Value co-creation can be achieved by interacting with healthcare providers and patients using integrated resources. Although research on the value of co-creation in healthcare has garnered attention, little effort has been made to systematically review the context of co-creation and the actors involved. This study aims to better understand value co-creation in healthcare from a management and business perspective. The research identifies the context of value co-creation, the actors involved, the theories adopted, the driving factors, the benefits, and the challenges faced. The Systematic Literature Review (SLR) method is used in this study, where 23 articles are identified and analyzed to answer a series of predetermined research questions. The article search was conducted using Harzing's Publish or Perish in 2022. The findings indicate that value co-creation benefits hospitals through competitive advantage, cost efficiency, profitability, and improved service quality. For patients, the perceived benefits include social experiences, patient centrality, and a better health community system.